Medicalising and Pharmaceuticalising Discourses in Food Supplement Advertising: A Multimodal Critical Discourse Analysis (MCDA) of Weight Loss Websites - Morgan, Katherine Rebecca Anne (2021)
The Internet has provided a window for the pharmaceutical industry into people’s domestic spaces and facilitated the advertisement and purchase of pharmaceutical goods (Fox et al., 2005d). Whilst direct to consumer marketing of pharmaceuticals, including weight loss pills, is not permitted in the UK, these marketing restrictions are bypassed by food supplement promotions (Ventola, 2011). Consequently, online sellers of potentially dangerous slimming pills are putting “desperate dieters’” health at risk by seducing them with the promise of “quick-fix” and discreetly procured weight loss solutions (U.K. Government, 2017). By examining the website data of four major purveyors of herbal weight-loss products, I explore the persuasive, discursive strategies that marketers employ to sell herbal weight loss pills as commercial products.